The Role of Job Satisfaction in Mediating Digital Competence and Innovation Culture on Employee Performance in MSMEs in Sidoarjo Regency - Qomari, Nurul; Musriha (Fakultas Ekonomi Universitas Kadiri, 2025)
This study aims to analyze the role of job satisfaction in mediating digital competence and innovation culture on employee performance in MSMEs in Sidoarjo Regency using a quantitative approach. The total sample in this study consisted of 389 respondents. Data were collected through questionnaires and processed using SmartPLS software to analyze the relationships between variables. The research findings indicate that digital competence influences job satisfaction. Innovation culture affects job satisfaction. Digital competence impacts employee performance. Innovation culture influences employee performance. Job satisfaction affects employee performance. Job satisfaction mediates the effect of digital competence on employee performance. Job satisfaction also mediates the effect of innovation culture on employee performance. The implications of this study suggest that MSMEs need to enhance digital competence and foster a strong innovation culture to drive job satisfaction, ultimately improving employee performance. These findings provide valuable insights for human resource managers in designing effective training programs and organizational development strategies. Additionally, the results can serve as a foundation for optimizing human resource management strategies to be more adaptive to changes in the business environment and technological advancements.